Mortality and failure of passive transfer of immunity in New Zealand dairy calves : a thesis presented in partial fulfilment of the requirements for the degree of PhD in Veterinary Science at Massey University, Manawatu, New Zealand - Cuttance, Emma Louise (Massey University, 2019)
In recent years, there has been a growing interest from consumers globally about the welfare of the animals producing their food. In New Zealand, particular attention has been paid to the treatment of calves though the help of welfare lobbyists bringing certain New Zealand farming practices into the spotlight. Unlike most of the rest of the world, in New Zealand, cattle are born outdoors and are housed only for a short period of time. This has meant that international research on mortality, colostrum management and calf health has been generally not applicable, and that we need New Zealand-based data to be able to benchmark key outcomes. We had two major objectives for this research. The first was to accurately estimate perinatal and postnatal mortality on New Zealand dairy farms and to identify potential risk factors. The second objective was to focus on one factor that is known to be strongly associated with calf mortality: the failure of the calf to take up sufficient colostral antibodies to provide protective immunity until the calf’s antibody-production system becomes fully effective (“failure of passive transfer”; FPT). The study aimed to estimate the prevalence of FPT across New Zealand dairy farms, identify potential risk factors that may be associated with that prevalence and to evaluate the effects of FPT to the end of first lactation. We found that, despite the significant differences between the New Zealand system and those of the northern hemisphere, the mortality risk of perinatal (5.7%) and postnatal calves up to weaning (4.1%), then weaning to ~27 months (2.7%) was comparable. However, our review of the previously published data highlighted that the quality of data collection, transparency in methods and validation of records in most other studies, particularly retrospective ones, was poor, limiting the validity of such comparisons. We identified substantial variation between farms in mortality risk (2.2-8.6% perinatal, 0-11% postnatal pre-weaning, 0-7.9% weaning to ~27 months), thus significant reductions in calf mortality may be achievable on many farms. One factor responsible for this variation may be farm-level prevalence of FPT which averaged at 33% and ranged from 5-84%. In intensive systems, separating calves from their dam and feeding high quality colostrum within 4-6 hours of birth reduces FPT. In contrast, our research found no effect of earlier colostrum feeding on FPT prevalence and the only significant herd level risk factors were region and herd size. This may be at least partly due to the difficulty of increasing calf pick-up to the frequency recommended for intensive farms. FPT increased mortality and morbidity and to a lesser extent decreased weight gain in the first 12 months, however showed no appreciable effect after this time.
This thesis comprises the published versions of articles listed on pp. 7-8. They are copyrighted to the New Zealand Veterinary Journal, The Veterinary Journal or the Journal of Dairy Science so have been removed, but may be accessed via the journals themselves.
Keywords: Calves; Dairy cattle; Mortality; New Zealand; Maternally acquired immunity; Colostrum; Calves; Dairy cattle; Health; 300904 Veterinary diagnosis and diagnostics